Services for people with complex psychosis: towards a new understanding. (June 2016) - Edwards, Tom; Macpherson, Rob; Commander, Martin; Meaden, Alan; Kalidindi, Sridevi
Summary: This paper describes the need for commissioners and service providers to consider the development of a whole-system approach to providing rehabilitation services for patients with complex psychosis, in the context of the current economic pressures and emergence of a competitive market in this area of mental health. The practical and organisational arrangements for the management of risk with such services are described, taking into account the varying provision of rehabilitation services across the UK and considering how these can be developed against the care clustering system and interfaces with other mental health services.